PATHOLOGICAL ANATOMICAL CHANGES, ETIOPATHOGENETIC MECHANISMS, AND CLINICAL-MORPHOLOGICAL FEATURES OF GANGRENE - Jumaniyozova Feruza Sayfiddinovna,; Jiyanmuradova Shakhlo Khamdamovna,; Ergasheva Shahzoda Abror qizi, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Annotation. This article presents analytical information related to pathological anatomy concerning gangrene. Gangrene is a severe pathological condition characterized by necrosis (death) of living tissues followed by putrefaction processes. The article describes its etiology, pathogenesis, and morphological changes. Gangrene occurs in several forms: dry, wet, gas, and internal gangrene, each having its own specific clinical and morphological features. Dry gangrene develops slowly and usually occurs without infection, whereas wet and gas gangrene progress rapidly and are complicated by infectious processes. Gas gangrene is particularly dangerous as it develops under the influence of anaerobic bacteria and poses a serious threat to the patient’s life. The article emphasizes that disturbances in blood circulation and metabolic changes in tissues play a crucial role in the pathogenesis of gangrene. In addition, detailed information is provided about clinical manifestations, complications, and modern treatment approaches. The management of gangrene requires urgent surgical intervention, antibiotic therapy, and detoxification measures. This analytical material contributes to understanding the main aspects of gangrene and demonstrates the practical importance of pathological anatomy.